Design of 8-bolt Stiffened Moment End Plates - Murray, Thomas M.; Kukreti, Anant R. (Engineering Journal, 1988)
This paper presents two design procedures for the 8-tension bolt, stiffened, extended, moment end plate shown in Fig. 1. The resulting end-plate design will be satisfactory for use in Type 1 construction (rigid-frame) as defined in Ref. 1 or, with appropriate modifications, as a FR type (fully restrained) connection as defined in the LRFD design notation.2 With bolt size limited to a maximum of 1½ in. dia., the configuration is capable of developing the full moment capacity of most available hotrolled beam sections. The two design procedures are limited to use with A36 steel and A325 bolts.